Penerapan Media Video Pembelajaran Untuk Meningkatkan Kemampuan Dasar Operasi Hitung Bilangan Bulat Siswa SMP Kelas VII - Nurlinda; Nenny Indrawati; Rezky Amaliyah (Lembaga Riset Ilmiah, 2023)
This study aims to improve the basic skills of integer arithmetic operations for class VII B students of SMP Negeri 2 Tinambung for the 2021/2022 academic year by using learning video media. This research is a class action research (classroom action research) with a research design using a modification of the Kemmis & McTaggart model which consists of 2 cycles with planning, implementing, observing, and reflecting stages. The subjects of this study were students of class VII B at SMP Negeri 2 Tinambung, which consisted of 34 students. The object of this research is to improve the basic skills of students' integer arithmetic operations through learning video media. Data collection techniques using instruments: (1) Observation sheets, (2) student ability tests, (3) student response questionnaires. Data analysis techniques were carried out in a quantitative descriptive and qualitative descriptive manner. The results showed that the average test result for students' integer arithmetic operations in cycle I was 70 with a learning completeness percentage of 68%, then in cycle II the average student score was 76.68 and the percentage of completeness was 85%. The results of the student response questionnaire to the learning process can be seen in cycle I being in the good category with an average value of 75% then increasing in cycle II by 85%. The results of observations of teacher and student activities can be seen in cycle I where the percentage of teacher activity was 78% and the percentage of student activity was 69%, then in cycle II the observations increased where the percentage of teacher activity reached 86% and the percentage of student activity reached 83%. With this it can be stated that the indicators of success in the tests of students' integer arithmetic operations ability, student response questionnaires and observation of teacher and student activities have been achieved in cycle II